Reorganization of the phycological herbaria of the Marine Sciences Institute, Federal University of Ceará (Brazil) - Dantas, Norma Pinheiro; Alves, Melissa Germana Lopes; Ribeiro, Daniele Sampaio; de Oliveira Neto, Júlio Mesquita (Arquivos de Ciências do Mar, 2018)
In this paper seaweed stuffs pertaining the collectiong period of years from 1949 to 1984 were reorganized and duely added to the Phycological Herbaria of the Marine Sciences Institute, Federal University of Ceará until 1997/98. A number of problems in the collection were detected. Consultion was made to the data sheets in the fichários and excicatas, numered and organized by division, order, family, genus and species. At the moment, the herbaria is comprised of a total of 1,306 lots and 3,014 specimens of marine algae, distributed in 25 orders, 57 families, 157 genera and 327 species. The Rhodophyta division is the most representative, with 61,9% of the lots, and 65,9% of the specimens and 56.6% of the species. The Chlorophyta division is represented by 23.4% of the lots, 22.7% of the specimens and 26.6% of the species. The Phaeophyta division, by 14.5% of the lots, 11.3% of the specimens and 15.9% of the species. The Cyanophyta and Xantophyta divisions are represented by 0.2% of the lots, 0,1% of the specimens and 0.9% of the species.